Green sustainable high-performance anti-aging rubber composite material and preparation method thereof

The rice husk-based silicon-carbon black hybrid filler is modified through vacuum ball milling process and green crosslinking is carried out in combination with bio-based epoxy soybean oil, which solves the problems of poor mechanical properties, easy aging and anti-aging agent migration pollution of rubber materials, and achieves a high-performance aging-resistant and recyclable rubber composite material.

CN119875220APending Publication Date: 2025-04-25FOSHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411966561.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing rubber materials are difficult to recycle, have poor mechanical properties, are prone to aging, and prevent the aging agent to migrate and contaminate.

Method used

The rice husk-based silicon-carbon black hybrid filler was modified through vacuum ball milling process, and green crosslinking was carried out in combination with bio-based epoxy soybean oil to prepare a green and sustainable high-performance aging-resistant rubber composite material.

Benefits of technology

The mechanical properties and aging properties of rubber composites are significantly improved, the slow release of anti-aging agents is achieved, migrating pollution is avoided, and the recycling of the material is achieved through transesterification reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875220A_ABST
    Figure CN119875220A_ABST
Patent Text Reader

Abstract

The invention discloses a green sustainable high-performance anti-aging rubber composite material and a preparation method thereof, and belongs to the technical field of sustainable rubber composite materials. Functional modification of the rice hull-based silicon carbon black hybrid filler is realized through a vacuum ball milling process, slow release of an anti-aging agent in a rubber matrix can be controlled, migration and emigration of a micromolecular anti-aging agent are avoided, interface bonding between the filler and rubber is remarkably enhanced, and the mechanical property of the rubber composite material is improved; more importantly, the prepared rubber composite material is low in cost, the raw materials are environmentally friendly, cyclic utilization can be achieved through transesterification, and the green and sustainable high-performance rubber composite material has important application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sustainable rubber composite materials, and specifically discloses a green, sustainable, high-performance, aging-resistant rubber composite material and a preparation method thereof. Background Art

[0002] Rubber is widely used in the pillar industries of the national economy, such as rail transportation, construction, and machinery. Among them, the cross-linking of rubber is the basis for achieving high elasticity and practical application of products. Since Charles Goodyear discovered the sulfur cross-linking technology in 1839, most rubbers have achieved chemical cross-linking through sulfur and peroxide. However, the traditional vulcanization method has problems such as poor solubility of the vulcanizing agent, easy migration, and easy reversion, which have a certain impact on the performance and environmental pollution of the vulcanized rubber. In order to improve the physical and mechanical properties of rubber materials, reinforcing fillers such as carbon black and white carbon black are usually added to the rubber matrix, but the production of the above-mentioned reinforcing fillers is energy-intensive and non-renewable. In recent years, although researchers have added bio-based fillers such as rice husk ash and rice husk silica to rubber to achieve certain reinforcement applications, the mechanical properties of rubber composites filled with rice husk ash are low, and the preparation of silica from rice husks is complex and costly.

[0003] On the other hand, most rubber materials contain unsaturated bonds. During processing, storage and use, they will experience serious aging due to the effects of light, heat, oxygen, ozone, stress, variable valence metal ions, high-energy rays, etc., which will affect the use of rubber products. At present, the most commonly used method in the rubber industry is to directly add a certain amount of antioxidant, but most rubber antioxidants are harmful to the human body or the environment, and small molecule antioxidants will migrate in the rubber matrix, resulting in the "frost" phenomenon of rubber products, which not only causes physical loss of antioxidants and affects their use efficiency, but also causes environmental pollution and threatens people's health. Therefore, how to achieve green cross-linking, high performance and sustainability of rubber materials, and synergistically solve the aging problem of rubber materials has become a bottleneck problem that needs to be solved in the rubber field. Summary of the invention

[0004] Based on this, in order to solve the problems of existing rubber materials being difficult to recycle, having poor mechanical properties, being easy to age, and being polluted by migration of antioxidants, the present invention provides a green, sustainable, high-performance, ageing-resistant rubber composite material and a preparation method. The specific technical scheme is as follows:

[0005] A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material, the preparation method comprising the following steps:

[0006] S1. Dissolve the rubber antioxidant in a solvent to prepare a rubber antioxidant solution with a mass fraction of 3%-6%, then add pyrolyzed rice husk, pour it into a vacuum ball mill after ultrasonic stirring, evacuate it, perform the first ball milling treatment, then add an epoxy silane coupling agent, perform the second ball milling treatment, centrifuge, wash and dry, and obtain a rice husk-based modified silicon-carbon black hybrid filler with both anti-aging and mechanical enhancement functions;

[0007] S2. Mixing the rice husk-based modified silicon-carbon black hybrid filler with carboxylated rubber, zinc oxide, and epoxidized soybean oil, and then vulcanizing the obtained mixed rubber to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

[0008] Furthermore, according to weight, 100 parts of carboxylated rubber, 5-50 parts of rice husk-based modified silicon carbon black hybrid filler, 3-10 parts of zinc oxide, and 5-15 parts of epoxidized soybean oil are included.

[0009] Further, in step S1, the rubber antioxidant is at least one of 4-aminodiphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 2-mercaptobenzimidazole, N-cyclohexyl-N'-phenyl-p-phenylenediamine, 2,2'-methylenebis-(4-methyl-6-tert-butylphenol), and 2,2'-thiobis(4-methyl-6-tert-butylphenol).

[0010] Furthermore, in step S1, the added amount of the rubber antioxidant is 3%-5% of the mass of the pyrolyzed rice husk.

[0011] Furthermore, in step S1, the solvent is at least one of ethanol, isopropanol, toluene, acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.

[0012] Furthermore, in step S1, the epoxy silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-(2,3-glycidyloxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0013] Furthermore, in step S1, the added amount of the epoxy silane coupling agent is 2%-5% of the mass of the pyrolyzed rice husk.

[0014] Furthermore, in step S2, the carboxylated rubber is at least one of carboxylated styrene-butadiene rubber and carboxylated nitrile-butadiene rubber.

[0015] Furthermore, in step S2, the temperature of the vulcanization treatment is 160°C to 180°C.

[0016] Compared with the prior art, this application has the following beneficial effects:

[0017] 1. Traditional rubber reinforcing fillers (such as carbon black, white carbon black, etc.) consume a lot of energy to produce and are non-renewable. In recent years, although researchers have added bio-based fillers such as rice husk ash and rice husk silica to rubber to achieve certain reinforcement applications, the mechanical properties of rubber composites filled with rice husk ash are low, and the preparation of silica from rice husks is complex and costly; and the above rubber composites are cross-linked by traditional vulcanization methods and cannot be recycled.

[0018] 2. The present invention realizes the functional modification of rice husk-based silicon-carbon black hybrid filler through vacuum ball milling process, which not only adsorbs the rubber antioxidant into the rice husk-based silicon-carbon black hybrid filler with high porosity and high specific surface area under the action of vacuum, but also realizes the slow release of the antioxidant in the rubber matrix, effectively avoids the migration of small molecule antioxidants, and solves the "flouring" problem of traditional antioxidants; but also significantly enhances the interface bonding between filler and rubber, and improves the mechanical properties of rubber composite materials; more importantly, through the green crosslinking of bio-based epoxidized soybean oil, the prepared rubber composite material can be recycled through ester exchange reaction, and this green, sustainable, high-performance rubber composite material has important application prospects.

[0019] 3. The present invention proposes a new method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material. The prepared rubber composite material has better comprehensive performance, the material is more green, environmentally friendly and renewable, the cost is lower, and the preparation method is simpler and more efficient. As a complete technical solution, it synergistically solves the bottleneck problems of existing rubber materials such as difficulty in recycling, poor mechanical properties, easy aging, and easy migration and pollution of antioxidants. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The SEM image and EDS mapping spectrum of the pyrolyzed rice husk used in Example 1;

[0021] Figure 2 This is a SEM image of the rice husk-based modified silicon-carbon black hybrid filler prepared in Example 1;

[0022] Figure 3 This is a cross-sectional SEM schematic diagram of the green, sustainable, high-performance, aging-resistant rubber composite material prepared in Example 1;

[0023] Figure 4 A schematic diagram of the cross-linked network structure of the green sustainable rubber composite material prepared in Example 1;

[0024] Figure 5 This is a cross-sectional SEM image of the rubber composite material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0027] A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material in one embodiment of the present invention comprises the following steps:

[0028] S1. Dissolve the rubber antioxidant in a solvent to prepare a rubber antioxidant solution with a mass fraction of 3%-6%, then add pyrolyzed rice husk, pour it into a vacuum ball mill after ultrasonic stirring, evacuate it, perform the first ball milling treatment, then add an epoxy silane coupling agent, perform the second ball milling treatment, centrifuge, wash and dry, and obtain a rice husk-based modified silicon-carbon black hybrid filler with both anti-aging and mechanical enhancement functions;

[0029] S2. Mixing the rice husk-based modified silicon-carbon black hybrid filler with carboxylated rubber, zinc oxide, and epoxidized soybean oil, and then vulcanizing the obtained mixed rubber to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

[0030] In one embodiment, in parts by weight, the carboxylated rubber is 100 parts, the rice husk-based modified silicon carbon black hybrid filler is 5-50 parts, the zinc oxide is 3-10 parts, and the epoxy soybean oil is 5-15 parts.

[0031] In one embodiment, in step S1, the rubber antioxidant is at least one of 4-aminodiphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 2-mercaptobenzimidazole, N-cyclohexyl-N'-phenyl-p-phenylenediamine, 2,2'-methylenebis-(4-methyl-6-tert-butylphenol), and 2,2'-thiobis(4-methyl-6-tert-butylphenol).

[0032] In one embodiment, in step S1, the amount of the rubber antioxidant added is 3%-5% of the mass of the pyrolyzed rice husk.

[0033] In one embodiment, in step S1, the solvent is at least one of ethanol, isopropanol, toluene, acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.

[0034] In one embodiment, in step S1, the epoxy silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-(2,3-glycidyloxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0035] In one embodiment, in step S1, the amount of epoxy silane coupling agent added is 2%-5% of the mass of the pyrolyzed rice husk.

[0036] In one embodiment, in step S1, the rotation speed of the first ball milling treatment is 300 rpm-800 rpm, and the time is 3h-10h.

[0037] In one embodiment, in step S1, the rotation speed of the second ball milling treatment is 300 rpm-800 rpm, and the time is 5h-10h.

[0038] In one embodiment, in step S2, the carboxylated rubber is at least one of carboxylated styrene-butadiene rubber and carboxylated nitrile-butadiene rubber.

[0039] In one embodiment, in step S2, the centrifugal speed is 3000 r / min to 8000 r / min.

[0040] In one embodiment, in step S2, the number of washings is 2-5 times.

[0041] In one embodiment, in step S2, the drying temperature is 60°C-120°C.

[0042] In one embodiment, in step S2, the temperature of the vulcanization treatment is 160°C to 180°C.

[0043] The above scheme can solve the problems of existing rubber materials being difficult to recycle, having poor mechanical properties, being easy to age, and being polluted by migration of antioxidants, and obtain a green, sustainable, high-performance, aging-resistant rubber composite material with better comprehensive performance, more green, environmentally friendly and renewable materials, and lower cost.

[0044] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0045] Embodiment 1:

[0046] A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material, the preparation method comprising the following steps:

[0047] 3 g of rubber antioxidant (2-mercaptobenzimidazole) was dissolved in 100 g of ethanol, and 100 g of pyrolyzed rice husk was added. After ultrasonic stirring for 2 h, the mixture was poured into a vacuum ball mill. After vacuuming, the mixture was ball milled at 300 rpm for 10 h. Then, 5 g of 3-glycidyloxypropyltrimethoxysilane was added, and the mixture was ball milled for 10 h. After centrifugal washing at 8000 r / min for 2 times, the mixture was dried at 120° C. to obtain a rice husk-based modified silicon-carbon black hybrid filler having both anti-aging and mechanical enhancement functions.

[0048] 50 parts by weight of the rice husk-based modified silicon-carbon black hybrid filler prepared in this embodiment, 100 parts by weight of carboxylated nitrile rubber, 3 parts by weight of zinc oxide and 10 parts by weight of epoxidized soybean oil are uniformly mixed, and then the mixed rubber is vulcanized at 180° C. to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

[0049] like Figure 1 As shown, Figure 1 This is a schematic diagram of the initial pyrolysis rice husk in Example 1. It has a relatively large size and a high porosity. From the elemental composition, it can be seen that it contains a large amount of silicon.

[0050] like Figure 2 As shown, Figure 2 Schematic diagram of the modified silicon-carbon black hybrid filler prepared in Example 1. Compared with pyrolyzed rice husk, the particle size is significantly reduced and more uniform.

[0051] like Figure 3 As shown, Figure 3 Schematic diagram of the cross-linked network structure of the high-performance aging-resistant rubber composite material prepared in Example 1.

[0052] Figure 4 This is the SEM image of the cross section of the composite material. It can be seen from the figure that the rice husk-based silicon carbon black hybrid filler has a strong interface with the rubber and is evenly dispersed in the rubber matrix without agglomeration.

[0053] The composite material prepared in Example 1 was made into a test sample, and the aging performance retention rate of the composite material of this example was determined using an aging box and a universal material tensile testing machine (the specific detection method is in accordance with conventional operations in the art and is not described in detail in this example). It was found that the tensile strength of the composite material prepared in this example reached 18.52 MPa, and after 5 days of thermal oxidative aging, the tensile performance retention rate was 91.94%, and after 15 days of thermal oxidative aging, the tensile performance retention rate was 81.25%.

[0054] Embodiment 2:

[0055] A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material, the preparation method comprising the following steps:

[0056] 4 g of rubber antioxidant (N-isopropyl-N'-phenyl-p-phenylenediamine) was dissolved in 100 g of ethanol, and 100 g of pyrolyzed rice husk was added. After ultrasonic stirring for 2 h, the mixture was poured into a vacuum ball mill, vacuumed, and ball milled at a speed of 500 rpm for 8 h. Then, 3 g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane was added, and the ball milling was continued for 5 h. After centrifugal washing at 5000 r / min for 3 times, the mixture was dried at 80 ° C to obtain a rice husk-based modified silicon-carbon black hybrid filler with both anti-aging and mechanical enhancement functions.

[0057] 30 parts by weight of the rice husk-based modified silicon-carbon black hybrid filler prepared in this embodiment, 100 parts by weight of carboxylated styrene-butadiene rubber, 10 parts by weight of zinc oxide and 15 parts by weight of epoxidized soybean oil were uniformly mixed, and then the mixed rubber was vulcanized at 180° C. to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

[0058] The test shows that the tensile strength of the composite material prepared in Example 2 reaches 12.37 MPa. After 5 days of thermal oxidative aging, the tensile property retention rate is 90.13%. After 15 days of thermal oxidative aging, the tensile property retention rate is 74.64%.

[0059] Embodiment 3:

[0060] A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material, the preparation method comprising the following steps:

[0061] 6 g of rubber antioxidant (N-cyclohexyl-N'-phenyl-p-phenylenediamine) was dissolved in 100 g of isopropanol, and 120 g of pyrolyzed rice husk was added. After ultrasonic stirring for 2 h, the mixture was poured into a vacuum ball mill, vacuumed, and ball milled at 800 rpm for 3 h. Then, 2.4 g of 3-glycidyloxypropyltriethoxysilane was added, and the mixture was ball milled for 8 h. After centrifugal washing at 3000 r / min for 5 times, the mixture was dried at 60° C. to obtain a rice husk-based modified silicon-carbon black hybrid filler having both anti-aging and mechanical enhancement functions.

[0062] 5 parts by weight of the rice husk-based modified silicon-carbon black hybrid filler prepared in Example 3, 100 parts by weight of carboxylated nitrile rubber, 5 parts by weight of zinc oxide and 5 parts by weight of epoxidized soybean oil were uniformly mixed, and then the mixed rubber was vulcanized at 180° C. to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

[0063] It is known from the test that the tensile strength of the composite material prepared in this embodiment reaches 8.45MPa, and after 5 days of thermal oxidative aging, the tensile performance retention rate is 92.47%, and after 15 days of thermal oxidative aging, the tensile performance retention rate is 83.14%. In addition, the recyclability of the composite material is further verified. After the prepared vulcanized rubber is crushed, it is swollen in tetrahydrofuran for 24 hours, diluted H2SO4 is added dropwise, and then stirred and refluxed at 70°C for 12 hours in a round-bottom flask equipped with a reflux device. The homogeneous mixed liquid is condensed in deionized water and filtered out with a Buchner funnel. After the solid phase is filtered out, it is dried to constant weight in an electric blast drying oven, and then the recycled rubber is added with 5 parts by weight of epoxy soybean oil in an open mill for rubber refining, and the mixed rubber is obtained and cross-linked at 180°C using a flat vulcanizer. It is known from the test that the tensile strength of the recycled composite material reaches 7.49MPa, which has good recyclability.

[0064] Comparative Example 1:

[0065] The difference between Comparative Example 1 and Example 1 is that the conventional atmospheric pressure alcohol grinding method is adopted, and the materials and dosages are consistent with those in Example 1, as follows:

[0066] 3 g of rubber antioxidant (2-mercaptobenzimidazole) was dissolved in 100 g of ethanol, 100 g of pyrolyzed rice husk was added, and after ultrasonic stirring for 2 h, the mixture was poured into a normal pressure ball mill and ball milled at 300 rpm for 10 h; then 5 g of 3-glycidyloxypropyltrimethoxysilane was added, and the ball milling was continued for 10 h. After centrifugal washing at 8000 r / min for 2 times, the silicon carbon black powder was obtained by drying at 120° C.;

[0067] 50 parts by weight of the silicon-carbon black hybrid filler prepared in Comparative Example 1, 100 parts by weight of carboxylated nitrile rubber, 3 parts by weight of zinc oxide and 10 parts by weight of epoxidized soybean oil were uniformly mixed, and then the mixed rubber was vulcanized at 180° C. to obtain a rubber composite material.

[0068] It can be seen from the test (the test conditions of the following comparative examples and embodiments are the same as those of Example 1) that the tensile strength of the composite material prepared in this comparative example is 16.35 MPa, which is lower than the strength of the composite material in Example 1. More importantly, after 5 days of thermal oxidative aging, the tensile property retention rate is reduced to 87.54%, and after 15 days of thermal oxidative aging, the tensile property retention rate is only 70.63%. This is mainly because, under normal pressure conditions, the ball milling efficiency of rice husk silicon carbon black is low, the particle size of the prepared hybrid filler is higher than that of Example 1, and because the antioxidant is not adsorbed into the rice husk silicon carbon black under normal pressure, the surface antioxidant not only affects the modification of the epoxy silane coupling agent, but also causes the silicon carbon black to agglomerate significantly (such as Figure 5As shown in the figure, the mechanical properties are relatively low, and in the subsequent centrifugal washing, this part of the antioxidant is easily lost by solvent washing, which seriously deteriorates its aging performance.

[0069] Comparative Example 2:

[0070] The type and amount of the rubber antioxidant in Comparative Example 2 are consistent with those in Example 1, the only difference being that the rubber antioxidant in Comparative Example 2 is directly added during the mixing process instead of being added during the ball milling process. Other modification methods and the formula composition of the rubber composite material are consistent with those in Example 1.

[0071] The tensile strength of the composite material of Comparative Example 2 was measured to be 18.34MPa. After 5 days of thermal oxidative aging, the tensile performance retention rate was reduced to 90.87%, which was basically the same as that of Example 1. However, after 15 days of thermal oxidative aging, the tensile performance retention rate was only 73.24%. This is mainly because the small molecule antioxidant in this comparative example is prone to migration during long-term use, and its long-term effectiveness is significantly reduced, and it causes pollution to the surrounding environment and human body; while the antioxidant in Example 1 can be adsorbed into rice husk silicon carbon black during vacuum ball milling, which limits the migration and migration of the small molecule antioxidant during use. This comparative example also further proves the advantages of vacuum ball milling modification.

[0072] Comparative Example 3:

[0073] Except for the epoxidized soybean oil, all other methods in Comparative Example 3 are consistent with those in Example 3. The only difference is that conventional sulfur is used for vulcanization in Comparative Example 3. Other methods for preparing rice husk-based modified silicon-carbon black hybrid fillers are consistent with those in Example 3.

[0074] The tensile strength of the composite material prepared in this embodiment is measured to be 8.53MPa. After 5 days of thermal oxidative aging, the tensile performance retention rate is 92.34%. After 15 days of thermal oxidative aging, the tensile performance retention rate is 84.07%. Compared with Example 3, it can be seen that the mechanical properties and aging properties of the composite material cross-linked with bio-based epoxidized soybean oil are basically consistent with the commercial sulfur-crosslinked rubber composite material. However, it is worth noting that after the prepared vulcanized rubber is crushed, it is swollen in tetrahydrofuran for 24h, diluted H2SO4 is added dropwise, and then stirred and refluxed at 70°C for 12h in a round-bottom flask equipped with a reflux device. The sample of the vulcanized rubber still maintains the initial state, is not dissolved, and cannot be recycled. By comparing Example 3 with this comparative example, it can be seen that the present invention uses epoxidized soybean oil for cross-linking treatment, which can not only achieve the performance of the current commercial sulfur-crosslinked composite material, but also has the characteristics of recyclability, which can effectively alleviate the solid waste pollution and resource waste of current rubber products.

[0075] In summary, the new method for functional modification of rice husk-based silicon carbon black hybrid filler using vacuum ball milling technology proposed in the present invention solves the migration and frosting problem of traditional small molecule antioxidants in the rubber matrix, significantly enhances the interface bonding between rice husk silicon carbon black and the rubber matrix, and the preparation method is simpler, more efficient and less expensive, which effectively improves the mechanical and aging properties of the rubber composite material; and through the green crosslinking of epoxidized soybean oil, the recyclable utilization of the rubber composite material is achieved. This green, sustainable, high-performance rubber composite material has important application prospects.

[0076] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a green, sustainable, high-performance, aging-resistant rubber composite material, characterized in that: The preparation method comprises the following steps: S1. Dissolve the rubber antioxidant in a solvent to prepare a rubber antioxidant solution with a mass fraction of 3%-6%, then add pyrolyzed rice husk, pour it into a vacuum ball mill after ultrasonic stirring, evacuate it, perform the first ball milling treatment, then add an epoxy silane coupling agent, perform the second ball milling treatment, centrifuge, wash and dry, and obtain a rice husk-based modified silicon-carbon black hybrid filler with both anti-aging and mechanical enhancement functions; S2. Mixing the rice husk-based modified silicon-carbon black hybrid filler with carboxylated rubber, zinc oxide, and epoxidized soybean oil, and then vulcanizing the obtained mixed rubber to obtain a green, sustainable, high-performance, aging-resistant rubber composite material.

2. The preparation method according to claim 1, characterized in that: According to weight, the carboxylated rubber is 100 parts, the rice husk-based modified silicon carbon black hybrid filler is 5-50 parts, the zinc oxide is 3-10 parts, and the epoxy soybean oil is 5-15 parts.

3. The preparation method according to claim 1, characterized in that: In step S1, the rubber antioxidant is at least one of 4-aminodiphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 2-mercaptobenzimidazole, N-cyclohexyl-N'-phenyl-p-phenylenediamine, 2,2'-methylenebis-(4-methyl-6-tert-butylphenol), and 2,2'-thiobis(4-methyl-6-tert-butylphenol).

4. The preparation method according to claim 1, characterized in that: In step S1, the added amount of the rubber antioxidant is 3%-5% of the mass of the pyrolyzed rice husk.

5. The preparation method according to claim 1, characterized in that: In step S1, the solvent is at least one of ethanol, isopropanol, toluene, acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.

6. The preparation method according to claim 1, characterized in that: In step S1, the epoxy silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-(2,3-glycidyloxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

7. The preparation method according to claim 1, characterized in that: In step S1, the added amount of the epoxy silane coupling agent is 2%-5% of the mass of the pyrolyzed rice husk.

8. The preparation method according to claim 1, characterized in that: In step S2, the carboxylated rubber is at least one of carboxylated styrene-butadiene rubber and carboxylated nitrile-butadiene rubber.

9. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the vulcanization treatment is 160°C to 180°C.

10. A green, sustainable, high-performance, aging-resistant rubber composite material, characterized in that: The green, sustainable, high-performance, aging-resistant rubber composite material is prepared by the preparation method according to any one of claims 1 to 9.